STUDI KANDUNGAN LOGAM BERAT DALAM DAGING IKAN DARI TAMBAK YANG DEKAT DAN YANG JAUH DARI DAERAH INDUSTRI - Indrajati Kohar; Ryanto Budiono; Diana Indriany; Nanik S. Wilujeng (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2005)
Water pollution lately is often becomes an important topic due to its correlation with health. Heavy metals that accumulated in human body mostly come from food. One kind of food that used to be contaminated by heavy metals is fish. Therefore it is interesting to study the heavy metals content in fish, whether it comes from industrial contaminated water. Study on the content of heavy metals Cr, Cu, Pb and Zn in ponds near and far from industrial areas has been conducted. The chosen areas were one from Sidoarjo area and one from Babat area, both are located in East Java. Samples were the meat of fish called tilapia (from Sidoarjo area), and milkfish and goldfish (from Babat area), also the water and mud from the ponds. Analytical method was wet destruction. Measurement of heavy metals content was done by Inductively Coupled Plasma Spectrometer (ICPS). In Babat area’s pond water was not found neither Cr, Cu, Pb nor Zn, while Zn was detected in Sidoarjo area’s, however, it was under the limit of detection. The mud of both ponds contained Cr, Cu, Pb and Zn. The goldfish contained only Cu and Zn, whereas the tilapia and milkfish contained Cu, Pb and Zn, however the metals content were not exceeded the maximum limit stated in the PPOM regulation No. 03725/B/SK/VII/89.